Community Perspectives on Religion-Based Schools in Indonesia - Efendi, Efendi; Afrina Rambe, Anggi; Cholik Yuswara Azmi, Muhamad; Asmaldi, Asmaldi (STIT Ahlussunnah Bukittinggi, 2023)
The interest of parents to send their children to the Integrated Islamic Elementary School is very high, even though the costs for schooling at the Integrated Islamic Elementary School are quite high. Compared to public schools in general, which are usually free (no fees).The aim of this study to find out as well as answer the question why Integrated Islamic Elementary Schools are in great demand by the Indonesian Muslim community, especially parents.This research uses the method Qualitatively using a case study approach, research data were taken through in-depth interviews with five people consisting of school principals, teachers, parents in Integrated Islamic Elementary Schools who were selected throughAnalysis Interactive Model Miles & Huberman. The results of this study show that the interest of parents in sending their children to Islamic elementary schools, this research shows that (i) theological factors are reasons based on religious considerations that parents want their children to have a strong religious foundation in addition to general education, of course. (ii) Sociological factors related to the increasing image of Islamic schools in the last decade in Indonesia. Different from previous times during the end of the new order and reform regime. (iii) Theological factors in the form of parents' desire for their children to be intellectually and spiritually intelligent.The results of this study can be used as initial information and data for future researchers in studying this problem in different contexts and issues.